DEMOCRATIC EDUCATION IN “MERDEKA BELAJAR” ERA - Khanif Maksum (PROGRES PENDIDIKAN, 2021)
Educational Democracy is a view of life that prioritizes equal rights and obligations as well as an equal treatment between educators and students in the learning process. Democracy in education contains elements of independence, freedom, and responsibility. An independent attitude to develop self-confidence and to be aware of one's limitations is very important to foster awareness that life in the community requires collaboration with other individuals. Freedom is defined as a life purpose that rests on the awareness of social pluralism, not solely on the interests of individuals or groups. Therefore freedom itself must be accompanied by a sense of full responsibility. The word "Educational Democracy" is two terms which are interrelated, democratic values ​​can be understood and owned by the community through educational activities, and vice versa so that education can produce output that has an independent attitude, has a critical thinking power, dynamic, democratic character and always upholds human dignity, then the implementation of education must be based on democracy so that the concept of independence in learning will grow well.